Calcium-magnesium-alumino-silicate induced degradation and failure of La2(Zr0.7Ce0.3)2O7/YSZ double-ceramic–layer thermal barrier coatings prepared by electron beam-physical vapor deposition. Issue 4 (April 2018) - Zhou, Xin; Wang, Jinshuang; Yuan, Jieyan; Sun, Junbin; Dong, Shujuan; He, Limin; Cao, Xueqiang
Abstract: Calcium-magnesium-alumino-silicate (CMAS) induced degradation of the La2 (Zr0.7 Ce0.3 )2 O7 /YSZ double-ceramic-layer thermal barrier coatings (TBCs) prepared by electron beam-physical vapor deposition (EB-PVD) was investigated in this study. CMAS reacted with La2 (Zr0.7 Ce0.3 )2 O7 to form a dense crystalline layer composed of apatite and fluorite phases, while the penetration was not arrested in the double-ceramic-layer coating due to the formation of vertical cracks during heat-treatment. In fact, the vertical cracks in the LZ7C3 layer inevitably provided efficient infiltration paths for molten CMAS to attack the bottom YSZ layer. Since the formation of Ca2 (La1-x Cex )8 (SiO4 )6 O26 apatite phase during CMAS reactions led to CaO enrichment in the melt, the YSZ buffer layer of the double-ceramic-layer coating even suffered a severer CMAS attack than the single YSZ coating.